PERTANGGUNGJAWABAN PIDANA TERHADAP APARAT KEPOLISIAN YANG MELAKUKAN KEKERASAN TERHADAP PENGUNJUK RASA - Samadi, Muhammad Alfarid; Erdianto, Erdianto; Tiaraputri, Adi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Police officers may not use violence in securing demonstrations. These provisions areregulated in Article 10 Letter C of the Republic of Indonesia's National Police Regulation Number8 of 2009 concerning the Implementation of Human Rights Principles and Standards in CarryingOut Duties of the Indonesian National Police, however cases of beatings against students fromagency Students Executivein Riau se musala RRI office district, Pekanbaru. Students who aremembers of bodies Student Executivethroughout Riau consist of Riau University (UNRI), RiauIslamic University (UIR), Suska State Islamic University (UIN), and Tabrani Rab University.There were about 37 students who were injured after clashing with the police. The studentsshowed a number of wounds, in the form of bruises on their hands, head and the lips that werebroken due to the impact of the rattan by the Sabhara members.This legal research is normative legal research that is oriented towards positive legalnorms (ius constitutum), namely: research that is more focused on the implementation of positivelegal norms and principles, in the form of a statutory approach that is relevant to study theformulation of the problem of legal issues in this legal research. In this study the authorsconducted a study that examines the analysis of law enforcement against violence perpetrated bylaw enforcement officials against protesters. With the formulation of the problem, how can thecriminal responsibility of the police who commit violence while securing a demonstration bereleased from punishment? What are the limits of violence that can and cannot be done insecuring a demonstration?The author concludes that police who commit violence in a demonstration can be heldresponsible for the crime, because they are state officials who function at the demonstration toprovide security, the violence is carried out consciously by the apparatus and the form of theerrors contained in the Criminal Code. In addition, the police have professional ethics that arecarried out when carrying out their duties, so that it confirms that officers who commit violencewhile securing a demonstration can be held responsible for criminals, and the limits on violencethat can and cannot be done in securing demonstrations are contained in Republic of IndonesiaNational Police Regulation Number 9 of 2003 Procedures for Providing Services, Safeguardingand Handling Cases for Submission of Opinions in Public in Articles 23 and 24Keywords: Accountability - Demonstrations - Police